High‐Performance Organic‐Inorganic Hybrid Photodetectors Based on P3HT:CdSe Nanowire Heterojunctions on Rigid and Flexible Substrates. (2nd October 2012) - Wang, Xianfu; Song, Weifeng; Liu, Bin; Chen, Gui; Chen, Di; Zhou, Chongwu; Shen, Guozhen
Abstract Organic‐inorganic hybrid photoelectric devices draw considerable attention because of their unique features by combining the relatively low ionization potential of the organic molecules and the high electron affinity of inorganic semiconductors. Hybrid organic‐inorganic poly(3‐hexylthiophene) (P3HT):CdSe nanowire heterojunction photodetectors are first demonstrated on silicon substrates, exhibiting a greatly enhanced photocurrent, a fast response, and a recovery time shorter than 0.1 s. Flexible hybrid photodetectors with excellent mechanical flexibility and stability are also fabricated on both poly(ethylene terephthalate) (PET) substrates and printing paper. The flexible devices are successfully operated under bending up to almost 180° and show an extremely high on/off switching ratio (larger than 500), a fast time response (about 10 ms), and excellent wavelength‐dependence, which are very desirable properties for its practical application in high‐frequency or high‐speed flexible electronic devices.